2016
DOI: 10.1007/jhep02(2016)038
|View full text |Cite
|
Sign up to set email alerts
|

A radiative model for the weak scale and neutrino mass via dark matter

Abstract: We present a three-loop model of neutrino mass in which both the weak scale and neutrino mass arise as radiative effects. In this approach, the scales for electroweak symmetry breaking, dark matter, and the exotics responsible for neutrino mass, are related due to an underlying scale-invariance. This motivates the otherwise-independent O(TeV) exotic masses usually found in three-loop models of neutrino mass. We demonstrate the existence of viable parameter space and show that the model can be probed at collide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…Once we introduce right-handed neutrino fields as SM gauge singlets they naturally possess a conformal and gauge-invariant, Majoranatype Yukawa coupling to the scalar singlet S. 10 Additionally, we obtain Dirac-type Yukawa couplings with the SM lepton and Higgs doublet. After electroweak symmetry breaking the Yukawa couplings lead to a neutrino mass matrix that realizes a type-I seesaw mechanism [15].…”
Section: Jhep07(2017)113mentioning
confidence: 99%
“…Once we introduce right-handed neutrino fields as SM gauge singlets they naturally possess a conformal and gauge-invariant, Majoranatype Yukawa coupling to the scalar singlet S. 10 Additionally, we obtain Dirac-type Yukawa couplings with the SM lepton and Higgs doublet. After electroweak symmetry breaking the Yukawa couplings lead to a neutrino mass matrix that realizes a type-I seesaw mechanism [15].…”
Section: Jhep07(2017)113mentioning
confidence: 99%
“…This can be realized at one loop [2], two loops [3], three loops [4,5], or four loops [6]. In [7] it has been shown that there is a class of three loop neutrino mass generation models, where the new particles that enter in the neutrino loop can be promoted to triplets [7], quintuplet [8], septuplets [9], and within a scale-invariant framework [10]. An interesting features of these class of models is that the scale of new physics can be of order TeV, making them testable at high energy colliders [11,12] (For a review, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and, in particular, studies of SI models for neutrino mass can be found in refs. [82][83][84][85][86][87][88][89][90][91][92].…”
Section: Jhep06(2016)182mentioning
confidence: 99%
“…None the less, as discussed in ref. [92] (and guided by ref. [95]), simple analytic expressions can be obtained by noting the following.…”
Section: Symmetry Breakingmentioning
confidence: 99%